PKM Usaha Kecil Menengah Kerajinan Karawo Di Kelurahan Padebuolo Kecamatan Kota Timur Kota Gorontalo Provinsi Gorontalo - Ariawan, Ariawan; Santoso, Budy (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2018)
Karawo's handicrafts as a superior cultural product of the region, is the identity and also the cultural heritagein Gorontalo City. However, the development of the two partners has problems both in terms of production process,management aspects, and marketing as well. The approach used in achieving the objectives of the CommunityPartnership Program (PKM) is a training method by practicing directly with partners, counseling with lectures,discussions and mentoring each partner and evaluation. The results of the Community Partnership ProgramImplementation (PKM) to overcome partner?s problems are: (a) Production aspects such as cooperating with thegovernment and producers/ distributors of raw materials, so that each partner has one distributor to fulfill raw materials,providing training and mentoring of motif designs using the computer program, so that each partner has skilled personnelin designing motifs using a computer program, Providing training and mentoring procedures and slicing techniques, sothat each partner has additional skilled personnel in the slicing process, Providing equipment / machinery assistance insupporting the production process, so that equipment / machinery is available in supporting the production process ineach partner. (b) Management aspects by providing training and mentoring to the management of business management,so that each partner has human resources who have knowledge and skills in business management. (c) Marketing aspectsby providing training and mentoring on promotion and marketing strategies through social media as well as the practiceof making online stores, so that each partner has the knowledge and insight on promotion and marketing strategies andhas one social media based online store that partners are able to manage by themselves